EFFECT OF ACTIVATED CHARCOAL PECAN SHELL (Aleurites moluccanus L. Willd) WITH VARIATIONS IN SULFURIC ACID CONCENTRATION ON DECREASED COD AND BOD LEVELS OF LAUNDRY LIQUID WASTE - Munadi, Rachmin; Azizah, Nurul (Universitas Tanjungpura, 2024)
Pecan shells are organic waste that can be decomposed but the texture is hard enough that it takes a long time to decompose it naturally. Various efforts to utilize pecan shell waste (Aleurites moluccanus L. Willd), one of which is as a raw material for making activated charcoal. This study aims to find out how the effect of pecan shell activated charcoal (Aleurites moluccanus L. Willd) with variations in the concentration of sulfuric acid against a decrease in Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) levels of laundry liquid waste, as well as the effectiveness of the concentration of sulfuric acid activators. The manufacture of pecan shell activated charcoal (Aleurites moluccanus L. Willd) as an adsorbent is carried out through two stages, namely the authoring stage and the activation stage. BOD testing is carried out by the Winkler titration method while COD is carried out by the closed reflux method. The concentration of sulfuric acid used is 0.5 N; 1.0 N; 1.5 N; 2.0 N; and 2.5 N with a soaking time of 2 hours. The results showed that the sulfuric acid activator that was most effective in reducing laundry liquid waste was at a concentration of 1.5 N with the largest decrease value for BOD, namely 955.56 mg/L (25.44 %) and for COD which was 1648.69 mg/L (18.56 %).